SAVINGS AND INVESTMENT IN THE MODERN WORLD - E. Starodubtseva (Вестник университета)
The article is devoted to consideration of the role and significance of the imbalances in the world economy - the ratio of investment and savings in the modern world. Proved the mechanism of the emergence of this imbalance as part of the modern development of the world economy. Shows the basic ways of reducing the disproportional nature of investments and savings.